Effectiveness and safety of cataract surgery in laminar air flow device versus traditional scrubs: A 1-year non-inferiority pilot study - Artus, Arnaud; Fabro, Filippo; Cochereau, Isabelle; Caputo, Georges; Tadayoni, Ramin; Vignal, Catherine; Galatoire, Olivier; Salviat, Flore; Gatinel, Damien; Panthier, Christophe (Frontiers in Medicine, 2023)
Purpose The study aimed to assess the safety and the non-inferiority of cataract surgery outside an operating room using the Surgicube®, a mobile laminar airflow (LAF) device. Settings This single-center study was conducted at the Rothschild Foundation, Paris, France. Design This is a retrospective cross-sectional study. Methods All patients operated on for cataracts using the Surgicube® between February 2020 and February 2021 were included and controlled by a cohort of patients operated on for cataracts in the traditional theater during the same period. Patients with a postoperative follow-up of less than 1 month were excluded. Data collection was carried out using the patient’s medical record. The primary endpoint was the evaluation of the number of endophthalmitis in the two groups. The secondary judgment criteria were the analysis of the various complications and the Logmar visual acuity at 1 month in the two groups. All the patients underwent an OCT retinal examination. Results A total of 923 randomized patients who underwent cataract surgery between 2020 and 2021 have been included in the study. Among them, 448 patients were operated on using the Surgicube, and 475 patients underwent surgery in the traditional operating room using the same lens phacoemulsification technique. There are no significant differences between the two groups (p > 0.05). Conclusion Cataract surgery using the Surgicube® outside a conventional operating room seems non-inferior to conventional scrub.